(untitled) (ҚазҰУ хабаршысы. Экономика сериясы, 2019)
The article considers the issue of digital transformation, which can become the basis for the further development of the principle of management by results of the state, since it allows you to overcome its previously identified limitations. The purpose of this article is a detailed study of new business models, including the so-called proactive service based on data, as well as the integration of modern fragmented information systems and communication channels. It is shown that despite the results achieved, problems associated with an insufficient level of openness, customer orientation and activity remain relevant. For example, government agencies are reluctant to disclose information that can be used to create added value in the form of relevant and relevant open data. The e-government development index (EGDI) in the Republic of Kazakhstan is analyzed. The results of the analysis revealed a high level of development of e-government. However, according to the authors, it is necessary to study in more detail new business models, including the so-called proactive service based on data, as well as the integration of modern fragmented information systems and communication channels to implement a multi-channel service model by creating a single “front office” aimed at providing the availability of information and services at anytime, anywhere and on any device (contact center, web portal, smart messengers, mobile applications, SMS messages).